Identification of Potential Land Locations for Green Open Space in Cirebon City Center (Case study: Pekalipan, Kesambi, and Kejaksan Districts) - Satar, Muhammad; Yosliansyah, Mohamad Rizalby; Yuniar, Nurrhisma (Universitas Negeri Semarang, 2023)
Society cannot ignore the rapid growth of Cirebon city, as evidenced by the population growth rate, which has increased by 2.91% per year compared to the surrounding area. This growth is expected to lead to an increase in built-up land and a reduction in green open spaces in Cirebon City, amounting to approximately 10.5%. This decline green space can increase urban temperatures, especially in Cirebon City. This study focuses on identifying potential locations for green open space from the macro scale of Cirebon City to the microscale in the city center. The analysis reveals a rise in temperature in the city center, with temperatures generally decreasing from the center to the periphery. Surface temperatures have shown an increase from 2015 to 2021, rising from 30.64°C in 2015 to 32.65°C in 2021. The main objective of this study is to identify potential green open space locations in Cirebon City Center. This research employs a quantitative, descriptive, and spatial approach, involving data collection through field observations and literature studies. The research methodology includes the utilization of remote sensing technology to process Landsat 8 images, which aids in the identification of potential green open space locations. The study results indicate that there is an area of 8.02 hectares, or 1.16%, that aligns with the Regional Detail Spatial Plan (RDTR) but necessitates efforts to enhance the quality of green open spaces through methods such as design, management, and community participation. Additionally, there is an area covering 681.42 hectares, not covered by the RDTR, which is a priority for greening through the implementation of green infrastructure.